Impact of COVID-19 pandemic on surgical neuro-oncology multi-disciplinary team decision making: a national survey (COVID-CNSMDT Study). Issue 8 (16th August 2020) - Price, Stephen John; Joannides, Alexis; Plaha, Puneet; Afshari, Fardad Taghizadeh; Albanese, Erminia; Barua, Neil U; Chan, Huan Wee; Critchley, Giles; Flannery, Thomas; Fountain, Daniel M; Mathew, Ryan K; Piper, Rory J; et al.
Abstract : Objectives: Pressures on healthcare systems due to COVID-19 has impacted patients without COVID-19 with surgery disproportionally affected. This study aims to understand the impact on the initial management of patients with brain tumours by measuring changes to normal multidisciplinary team (MDT) decision making. Design: A prospective survey performed in UK neurosurgical units performed from 23 March 2020 until 24 April 2020. Setting: Regional neurosurgical units outside London (as the pandemic was more advanced at time of study). Participants: Representatives from all units were invited to collect data on new patients discussed at their MDT meetings during the study period. Each unit decided if management decision for each patient had changed due to COVID-19. Primary and secondary outcome measures: Primary outcome measures included number of patients where the decision to undergo surgery changed compared with standard management usually offered by that MDT. Secondary outcome measures included changes in surgical extent, numbers referred to MDT, number of patients denied surgery not receiving any treatment and reasons for any variation across the UK. Results: 18 units (75%) provided information from 80 MDT meetings that discussed 1221 patients. 10.7% of patients had their management changed—the majority (68%) did not undergo surgery and more than half of this group not undergoing surgery had no active treatment. There was marked variation across the UK (0%–28% change in management). Units that did not change management could maintain capacity with dedicated oncology lists. Low volume units were less affected. Conclusion: COVID-19 has had an impact on patients requiring surgery for malignant brain tumours, with patients receiving different treatments—most commonly not receiving surgery or any treatment at all. The variations show dedicated cancer operating lists may mitigate these pressures. Study registration: This study was registered with the Royal College of Surgeons of England's COVID-19 Research Group (https://www.rcseng.ac.uk/coronavirus/rcs-covid-research-group/ ).